Oxygen-Containing Functional Groups Regulating the Carbon/Electrolyte Interfacial Properties Toward Enhanced K+ Storage - Peng, Yufan; Chen, Zhen; Zhang, Rui; Zhou, Wang; Gao, Peng; Wu, Jianfang; Liu, Hui; Liu, Jilei; Hu, Aiping; Chen, Xiaohua (Nano-Micro Letters, 2021)
Oxygen-containing functional groups were found to effectively boost the K+ storage performance of carbonaceous materials, however, the mechanism behind the performance enhancement remains unclear. Herein, we report higher rate capability and better long-term cycle performance employing oxygen-doped graphite oxide (GO) as the anode material for potassium ion batteries (PIBs), compared to the raw graphite. The in situ Raman spectroscopy elucidates the adsorption-intercalation hybrid K+ storage mechanism, assigning the capacity enhancement to be mainly correlated with reversible K+ adsorption/desorption at the newly introduced oxygen sites. It is unraveled that the C=O and COOH rather than C-O-C and OH groups contribute to the capacity enhancement. Based on in situ Fourier transform infrared (FT-IR) spectra and in situ electrochemical impedance spectroscopy (EIS), it is found that the oxygen-containing functional groups regulate the components of solid electrolyte interphase (SEI), leading to the formation of highly conductive, intact and robust SEI. Through the systematic investigations, we hereby uncover the K+ storage mechanism of GO-based PIB, and establish a clear relationship between the types/contents of oxygen functional groups and the regulated composition of SEI. Highlights: 1 Oxygen functional groups improve rate capability as well as long-term cycling stability of graphite oxide. 2 The adsorption-intercalation hybrid K+ storage mechanism of graphite oxide (GO) is elucidated by in situ Raman spectroscopy and systematic electrochemical characterization. 3 It is unraveled that the C = O and COOH rather than C-O-C and OH groups contribute to the formation of highly conductive, intact and robust solid electrolyte interphase.